'Shopping for Voice': Do Pre-Existing Non-Union Representation Plans Matter When Employees Unionize? - Timur, Ahmet Tarik; Taras, Daphne Gottlieb; Ponak, Allen M. (My University, 2012)
The transition to unionization in three workplaces with pre-existing non-union employee representation plans (NERPs) is contrasted to three matched sites, which had only individual representation. Pre-existing collective voice arrangements had substantial effects on the process and outcomes of unionization. While the individual representation sites presented a conventional process of mobilization and attachment to the union, the NERP sites revealed a more equivocal outcome. The union was used in an instrumental manner to increase NERP power and to achieve worker demands already articulated by the NERP. NERP leaders became union leaders. There remained significant attachment to the NERP and a reluctance to fully embrace unionization. © 2011 Blackwell Publishing Ltd/London School of Economics.